Influence of the Drug Detralex on Calcium Ion-dependent Smooth Muscle Contractility, Function of an Endothelium and Aggregation of Thrombocytes in the Conditions of Experimental Modeling of Endothelial Dysfunction - Soldatov, Vladislav O. (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: The phlebotropic effect of flavonoids is contradictory, and clinically significant effects are poorly understood theoretically. The efficiency of flavonoids needs verification by means of the large-scale experimental and clinical trials protected from the conflicts of interest. Research Tasks: Experimental study of venotonic, anti-aggregation and endothelioprotectiv properties of the drug Detralex 1000 mg. Materials and Methods: A venotonic effect was investigated after week administration of drug inside on model of the endotelium-dependent smooth muscle response to increased calcium ion isolated portal vein of rats. The Biopac Bas System Station installation including a polygraph of Biopac MP 150 with the TSD-104A module and the software of ACQ 4.2 was for this purpose used. The protective properties of the endothelium were studied on a 7-day model of L-N-nitro-L-arginine-methyl ether-induced rat endothelial dysfunction using invasive blood pressure recording. Aggregation of thrombocytes (AT) was investigated by a visual micromethod with use as inductors ADF, a collagen, thrombinum, ristomycinum, and adrenaline. Results: In model of endothelial dysfunction rising of sensitivity to the contractile response to Ð¡a2+ the isolated segment of a portal vein after use of the drug Detralex of 500 mg/kg per day, and also elongation of AT and decrease of coefficient of endothelial dysfunction on a background the course reception of the investigated preparation. Conclusion: Pleiotropic effect of micronized combination of diosmin and hesperidin, expressed in strengthening the contractile potential of smooth muscle veins, improving endothelial function, and lengthening thrombocyte aggregation, was Ñonfirmed.